Employees’ mental health issue during covid-19: A review - Habibi Aripin; Carol Hiew Ka Low; Julazrie Benjamin; Lee Yee Fang; Nicky Welly James; Nurul Syafia Syahwanie Al-amin; Roslinah Mahmud (Universiti Malaysia Sabah, 2021)
Coronavirus (COVID-19) is an infectious disease that results in persistent pandemics and affects the global economy, society, political, psychology and environment around the world. It is important to realize that it could affect individual in different ways including resulting in the mental health and well-being of employees. Therefore, the purpose of this study is determinants the causes of the rising in mental health issue among employees during Covid-19 and finally to suggest recommendations to reduce the outcomes of COVID-19 on employees’ mental health. This paper is a review of the literature. Article searches are made in Google, Web Science and Semantic scholars. We use a combination of terms related to coronavirus, workplace and mental health. The result of this study shows that financial concern and instability of jobs, stigma and social exclusion, quarantine and isolation, fear or anxiety of exposure to the virus, and changes in the new workplace environment are the causes of the rising in mental health issue among employees during COVID-19. Furthermore, stigma protection, social support, return-to-work schedule development, mitigate the psychological effects of quarantine and training are suggestion that have been recommend reducing the outcomes of COVID-19 on employees’ mental health.